2012
DOI: 10.1111/j.1398-9995.2012.02860.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergy to deamidated gluten in patients tolerant to wheat: specific epitopes linked to deamidation

Abstract: Background Gluten proteins can be modified by deamidation to enhance their solubility and technological applications. However, severe allergic reactions have been reported after the consumption of food products containing deamidated gluten (DG) in subjects tolerant to wheat. This work aimed to characterize allergen profiles for these patients in comparison with those of patients allergic to wheat and to identify IgE‐binding epitopes. Methods Sera were obtained from 15 patients allergic to DG and from nine pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
50
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 29 publications
7
50
1
2
Order By: Relevance
“…or orally with acid-hydrolysed gluten developed specific IgG 1 responses with a binding capacity different from that in rats sensitised with unmodified gluten. This is in agreement with Denery-Papini et al [41], who found that IgE from patients allergic to deamidated gluten had the strongest reaction, with an epitope where 2 or 3 of 4 glutamines were changed to glutamate due to deamidation.…”
Section: Discussionsupporting
confidence: 82%
“…or orally with acid-hydrolysed gluten developed specific IgG 1 responses with a binding capacity different from that in rats sensitised with unmodified gluten. This is in agreement with Denery-Papini et al [41], who found that IgE from patients allergic to deamidated gluten had the strongest reaction, with an epitope where 2 or 3 of 4 glutamines were changed to glutamate due to deamidation.…”
Section: Discussionsupporting
confidence: 82%
“…This is in line with results presented by Denery-Papini et al . [33] who found that IgE from patients allergic to gluten deamidated by heating and acid treatment reacted strongest with an epitope where two or three glutamines were deamidated to glutamic acid. These data supports our finding, that acid hydrolysis of gluten induces formation of new epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to clarify if the raised HWP-specific IgE can be a result of cross-reactions of wheat-specific IgE to HWP or possibly be a double sensitization by wheat and HWP. In addition, Denery-Papini et al [30] showed recently that this type of allergy to deaminated gluten has a separate entity, which is characterized by a homogeneous IgE-Ab response, and is a direct consequence of present technologies applied to industrial food products. We found that most children with IgE-Ab <8 kU A /l to HWP did not react in CD-sens to HWP in comparison to those with higher IgE-Ab levels.…”
Section: Discussionmentioning
confidence: 99%